2018
DOI: 10.12788/ajo.2018.0056
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent Perioperative Hypothermia During Orthopedic Surgery

Abstract: Inadvertent perioperative hypothermia is a significant problem in patients undergoing either emergency or elective orthopedic surgery, and is associated with increased morbidity and mortality. Though in general the incidence of inadvertent perioperative hypothermia in postoperative recovery rooms has been decreasing over the last 2 decades, it still remains a significant risk in certain specialty practices, such as orthopedic surgery. This review article summarizes the currently available evidence on the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…[3][4][5][6][7][8] It has been reported that hypothermia is associated with perioperative complications such as blood loss, wound infection, shivering, and mortality. 1,[9][10][11][12][13] Therefore, perioperative heat retention methods to prevent perioperative hypothermia such as providing a warmed blanket and active patients warming are important. 3,9,10,13 Risk factors associated with hypothermia have been surveyed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8] It has been reported that hypothermia is associated with perioperative complications such as blood loss, wound infection, shivering, and mortality. 1,[9][10][11][12][13] Therefore, perioperative heat retention methods to prevent perioperative hypothermia such as providing a warmed blanket and active patients warming are important. 3,9,10,13 Risk factors associated with hypothermia have been surveyed.…”
Section: Introductionmentioning
confidence: 99%
“…1,[9][10][11][12][13] Therefore, perioperative heat retention methods to prevent perioperative hypothermia such as providing a warmed blanket and active patients warming are important. 3,9,10,13 Risk factors associated with hypothermia have been surveyed. 3,4,9,13 Although major surgery, requiring a long operative time, and young (pediatric) patient age are noted as risk factors, 3,9 only a few studies focus on hypothermia as an intraoperative complication in pediatric scoliosis surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results corroborate the results of other studies, in which these variables were associated with the development of hypothermia. 10,12 In the present study, preoperative temperature was also considered a risk factor for developing hypothermia. Body temperature before anesthetic induction shows the heat content in peripheral tissues and the center-periphery temperature gradient, which will interfere with the magnitude of body temperature redistribution that occurs mainly in the first surgical hour.…”
Section: Discussionmentioning
confidence: 95%
“…It is noteworthy that the association of two or more risk factors predisposes any type of surgical patient to develop hypothermia. 10 Age-related risk is related to age extremes. In the elderly, the senescence process causes changes in the thickness of the skin layers, which can interfere with the maintenance of body heat; 3 children, in turn, have a smaller body surface and reduced regulatory capacity.…”
Section: Discussionmentioning
confidence: 99%